2018
DOI: 10.5194/nhess-2018-230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the impact of SSTs on a simulated medicane using ensemble simulations

Abstract: Abstract. The sensitivity of the October 1996 medicane in the western Mediterranean basin to sea surface temperatures (SSTs) is investigated via 24-member ensembles of regional climate model simulations. Eleven ensembles are created by uniformly changing SSTs in a range of −4 K to +6 K from the observed field, with a 1 K step. By using a modified phase space diagram and a simple compositing method, it is shown that the SST state has a minor influence on the tracks of the cyclones, but a strong influence on the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…That the use of domain shifting techniques is a valuable tool for estimating uncertainties in RCM ensemble simulations, has been shown in several studies (e.g. Pardowitz et al, 2016;Mazza et al, 2017;Noyelle et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…That the use of domain shifting techniques is a valuable tool for estimating uncertainties in RCM ensemble simulations, has been shown in several studies (e.g. Pardowitz et al, 2016;Mazza et al, 2017;Noyelle et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the cyclone can be self‐sustaining, as delineated in the following: (a) Deep convection contributes to the decrease of the cyclone central pressure once air is transported from the lower to the upper levels; (b) a lower central pressure minimum implies stronger pressure gradients with the neighboring areas and, consequently, more intense low level winds; (c) stronger winds increase the turbulent heat fluxes from the sea to the atmosphere (and, consequently, increase evaporation; Zeng et al, ); and (d) the chain of physical processes continues (feedback mechanism): With a more intense cyclone, the sea‐air fluxes increase, and the system continues to strengthen. This sequence of processes is known as WISHE theory for tropical cyclone development (Emanuel, , ), and the same processes explain the intensification of tropical‐like cyclones in the Mediterranean Sea (Cioni et al, ; Miglietta et al, , ; Miglietta & Rotunno, ; Noyelle et al, ; Tous & Romero, ). In the present study, part of the a–d sequence of processes can be observed in Figures b and c.…”
Section: Resultsmentioning
confidence: 98%
“…Following Gozzo et al (), over the SAO, a cyclone can be classified as subtropical when B < 25, −V T L > −50, and −V T U < −10. As pointed out by Noyelle et al (), the B parameter is sensitive to the exact location of the cyclone center (i.e., it captures the local information), while −V T U on its own is more suitable to capture the cyclone environment. Hart's algorithm to compute the CPS requires the track of the cyclone and the geopotential height at three pressure levels (900, 600, and 300 hPa).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ensemble is then created using the domain-shift technique (e.g. Rezacova et al, 2009;Pardowitz et al, 2016;Noyelle et al, 2018). In this approach, a central domain is defined and the domain centre is systematically shifted five grid cells (∼0.55 • ) in the cardinal and ordinal directions N, NE, E, SE, S, SW, W and NW, giving perturbed initial and boundary conditions for each ensemble member (see Rezacova et al (2009) and Mazza et al (2017) for illustrative schematics).…”
Section: Climate Simulationsmentioning
confidence: 99%